Ventriculo-Peritoneal Shunt Infection: Three Years Experience in Combined Military Hospital, Dhaka - Choudhury, Ahmed ul Mursalin; Salek, Md Al Amin; Faisal, Hasnayen; Islam, Md Aminul (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Treatment of Hydrocephalus by placement of Ventriculo-peritoneal (V-P) Shunt is a common neurosurgical practice. But presence of shunt predisposes to increased infection. Objective: To focus on aetiological factors for developing shunt infection. Methods: This prospective observational study was carried out at Neurosurgery Center, Combined Military Hospital, Dhaka during the period of June 2015 to May 2018. A total of 33 patients were included in the study, all of them underwent CSF shunt surgery at this centre. They were followed up for one month after surgery. Age, sex and socioeconomic condition of the patients, types (obstructive or communicating) of hydrocephalus (HCP), aetiology of HCP, duration of surgery, shunt type used and routine or emergency surgery were the factors that were analysed for possible association with infection. Results: Eight (24.2%) patients developed shunt infection, among whom infants and male were predominate. Low socio-economic group, prolonged operation time and emergency surgery were found to have association with increased rate of infection. Conclusion: V-P shunt insertions had unacceptably high infection rate despite the presence of a protocol for the procedure. A protocol should be developed for strict compliance and where possible, alternative procedure Endoscopic Third Ventricullostomy (ETV) or External Ventricular Drain (EVD) should be employed to minimize shunt infection. JAFMC Bangladesh. Vol 18, No 1 (June) 2022: 16-18